Atenção à tuberculose em um município de tríplice fronteira internacional: o ensino como perspectiva para reorientação da assistência - Campos, Regiane Bezerra (2016)
Tuberculosis has a rising and prevalent history in the municipality of Foz do Iguaçu. Due to the epidemiological and ephemeral reality of health conditions, the overcoming of fragmentation in care systems, the adoption of a care model that would focus on the health care system and on the community and changes in behavior in permanent health education are highly relevant. Current analysis analyze the impairing issues in the care of tuberculosis in the municipality of Foz do Iguaçu PR Brazil, by a descriptive and quantitative assessment on the organization in the care of tuberculosis, integration with the community, self-care, decision bearing and an outline of health services system. One hundred and five health professionals from 14 health care units were interviewed. They were provided with a questionnaire from the MacCooll Institute for Health Care Innovation, which was adapted and validated in Brazil by Moyses et al. (2012) and by Villa (2013) for the assessment of the control of tuberculosis. Classified as basic, Integration with the community, with mean 3.2 (DP+-1.8); integration with factors of the care model to people with TB, with mean 5.3 (DP+-1.6); and decision-bearing, with mean 5.8 (DP+-2.1) had the worst results. Best performance occurred with supported self-care, with an average of 6.9 (DP+-2.1); organization of care in Tuberculosis, with an average of 6.2 (DP+-1.5); outline of health services system, with an average of 6.6 (DP+-1.7); and systems in clinical information, with an average of 6.3 (DP+-1.8), all classified as moderate. Results show the need of professional capacitation and observance of the principles and guidelines of programs/policies for the control of Tuberculosis in First Health Care and in the National Service Health System (SUS). The theoretical and technological proposal in teaching is a challenge. It would promote behavior changes based on the management of chronic health conditions, in the institutions concerned.